2008
DOI: 10.1016/j.ijgo.2008.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Burn injuries during pregnancy in Iran

Abstract: Inhalation injury, suicidal burn injury, and percentage of TBSA burned were correlated with a higher maternal and fetal mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
4
13
0
Order By: Relevance
“…Most of the maternal mortality (40%) had TSAB above 30%. Kamini et al 9 also showed in their study that the maternal and fetal mortality rates were higher when the burn was suicidal. Higher degree of burn is directly proportionate to severity of outcome.All third degree burn (n=4) resulted in poor outcomes in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Most of the maternal mortality (40%) had TSAB above 30%. Kamini et al 9 also showed in their study that the maternal and fetal mortality rates were higher when the burn was suicidal. Higher degree of burn is directly proportionate to severity of outcome.All third degree burn (n=4) resulted in poor outcomes in our study.…”
Section: Discussionmentioning
confidence: 86%
“…The main predictor of the survival of pregnant woman is the percentage of total body surface area affected (5). In most cases in which both the mother and the fetus died, the total body surface area was more than 40% (5,7,8,10,21).…”
Section: Discussionmentioning
confidence: 99%
“…Most unintentional burns occur in the home around the cooking area, with flames being the major cause (4). Women of reproductive age are often victims of burn injury in developing countries (5). Burns that occur during pregnancy are uncommon; however, these injuries are often fatal for both the pregnant mother and her fetus, especially in low-income countries (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations